End-plate potentials in a model muscle fiber. Corrections for the effects of membrane potential on currents and on channel lifetimes. - Van der Kloot, W (1984)
At the neuromuscular junction, the end-plate potential is generated by a conductance increase in the end-plate membrane. The end-plate depolarization brings the membrane potential toward the reversal potential, which diminishes the driving force for inward current flow. A. R. Martin (1955, J. Physiol. [Lond.]. 130:114-122) devised a simple formula to correct end-plate potential amplitudes for a diminished driving force based on a purely resistive model of the end-plate membrane. The model ignores the membrane capacity, the complexity of the equivalent circuit for a muscle fiber, the variation in channel lifetimes with changes in membrane potential, and the extension of the end plate along a length of the cable. We have developed a model that incorporates all of these features. The calculations show that Martin's correction is, in theory, quite satisfactory for a cable that has the characteristics of a muscle fiber unless the recording is made at a distance from the site of inward current flow. However, there is a discrepancy between models of the frog neuromuscular junction and the available experimental data, which suggests that the end-plate depolarization produced by a given current is greater than expected from their model.